PENERAPAN VECTOR AUTOREGRESSIVE (VAR) DALAM MEMPREDIKSI RETURN SAHAM DI INDONESIA - Seftina Diyah Miasary (Department of Mathematics Education, Universitas Kuningan, 2022)
The rate of return (return) and risk are inseparable in investing activities. One equilibrium model that describes the relationship between return and risk assumes that the expected return is influenced by more than one macroeconomic factor. Furthermore, the causal relationship between stock returns and macroeconomic factor returns was analyzed using VAR. The application of VAR in this study is to predict stock returns through the stages of checking data stationarity, determining the optimal lag length, testing Granger causality between variables, estimating VAR model parameters and Portmanteau diagnostic tests, and predicting stock returns. The results show that the VAR (1) model is the most appropriate model to describe the relationship between stock returns and macroeconomic factor returns with a significant model owned by BBCA, ICBP, INTP, KLBF, and SMGR stocks. Furthermore, the VAR (1) model is used to predict the five stock returns. The prediction results show that INTP's stock returns are negative while the returns of the other four stocks are positive. This shows that INTP shares experienced a capital loss, while the stock returns of BBCA, ICBP, KLBF, and SMGR experienced capital gains